Regulasi Diri dalam Belajar Siswa Berprestasi kelas 5 di SDN 9 Mataram Tahun Ajaran 2020/2021 - Diaz Diaz; Darmiany Darmiany; Itsna Itsna (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2021)
This study aims to examine the ability of self-regulation in the learning of fifth-grade outstanding students at SDN 9 Mataram. The self-regulatory ability factors, dimensions of self-regulation ability, aspects of self-regulation ability. This study uses a descriptive qualitative research method with an ethnography approach. The techniques of data collection used interviews and documentation. The data analysis used the Milles and Huberman model, namely data condensation, data presentation, and drawing conclusions. The results of this study indicate the ability of self-regulation in high achieving students in grade 5 at SDN 9 Mataram that the study habits of outstanding students are already able to set learning goals, make study schedules at home, ask teachers when they have difficulties in learning, and look for tutorials on youtube. After learning, students repeat the material that has been learned and then make a small summary of the learning outcomes.